Zakonodaja in pravni okviri gojenja tujerodnih drevesnih vrst v gozdovih Slovenije - Pia Carolie Adamič; Robert Brus; Kristjan Jarni (Acta Silvae et Ligni, 2022)
The aim of the study was to review the legislation and legal framework for the cultivation of non-native tree species in Slovenian forests. In the EU, several legal instruments are relevant for the introduction, use and management of non-native tree species, e.g. the Council Directive on the marketing of forest reproductive material, the Habitats Directive and the Regulation on the prevention and control of the introduction and spread of invasive alien species. In Slovenian legislation, the area of their introduction and potential impact is regulated primarily by the Nature Conservation Act, but also important are the Decree on Special Protection Areas (Natura 2000 areas), the Forest Act, the Forest Reproductive Material Act, the Regulations on the Designation of Seed Areas and the Decree on Protected Wild Plant Species. According to the legislation, the cultivation of non-native trees is not prohibited in Slovenia for the implementation of forestry activities, immigration is allowed, and the introduction of new non-native species requires an appropriate procedure that includes an environmental impact assessment and is approved by the competent minister. Slovenian legislation thus provides opportunities for the cultivation of non-native tree species, which could be of crucial importance for the adaptation of forests to climate change due to their better resistance to biotic and abiotic factors, as well as of economic importance due to their faster growth and timber quality.